2021
DOI: 10.7759/cureus.12622
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte, Lymphocyte-to-Monocyte, and Platelet-to-Lymphocyte Ratios: Prognostic Significance in COVID-19

Abstract: Background and objective Neutrophils are primarily responsible for activating the immune system, and systemic inflammation destroys CD4+ T lymphocytes and increases suppressor CD8+ T lymphocytes, thereby leading to an increased neutrophil-to-lymphocyte ratio (NLR). An increase in the apoptosis of lymphocytes leads to lymphopenia and elevated thrombopoietin (THPO) promotes megakaryocyte production. The reflections of these inflammatory changes can be vital in gauging the progression of the disease. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
(15 reference statements)
1
16
0
2
Order By: Relevance
“…On the other hand, the abundance of CD8+ T cells was reported to decrease in COVID-19 patients and exhibit functional exhaustion molecules, such as NKG2A, PD-1, and TIM-3 [87]. And neutrophil-to-lymphocyte can also increase as a result of systemic inflammation serving as a prognostic marker [88]. Single-cell RNA sequencing of bronchoalveolar cells depicted a more complicated landscape of CD8+ T cells in COVID-19 patients, further pointing out the heterogeneity of cell numbers and clonal expansion of different CD8+ T cell clusters [89].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the abundance of CD8+ T cells was reported to decrease in COVID-19 patients and exhibit functional exhaustion molecules, such as NKG2A, PD-1, and TIM-3 [87]. And neutrophil-to-lymphocyte can also increase as a result of systemic inflammation serving as a prognostic marker [88]. Single-cell RNA sequencing of bronchoalveolar cells depicted a more complicated landscape of CD8+ T cells in COVID-19 patients, further pointing out the heterogeneity of cell numbers and clonal expansion of different CD8+ T cell clusters [89].…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation was seen between the T lymphocyte percentage and the NLR (r = −0.212, P = 0.037), CRP (r = −0.536, P < 0.001) and with the D-Dimer levels (r = −0.326, P = 0.001), as shown in Table 4 . These three above mentioned parameters are well-established severity markers, 24 bolstering the T lymphocyte percent’s prognostic usefulness in COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“… 23 In terms of the PLR, Bg et al previously indicated that PLR has a predictive value in COVID-19 investigations, but this finding was not confirmed in our study. 24 Kalabin et al cautioned against using both the NLR and the PLR as independent markers of illness severity. 25…”
Section: Discussionmentioning
confidence: 99%
“…Severe < 100 (45% mortality) = hospitalization. iv) Ratio: neutrophils/lymphocytes (RNL) [55]- [61]. v) Platelet/lymphocyte ratio (PLR) [60] [61] [62].…”
Section: Criteria Of Hospitaizationmentioning
confidence: 99%